Young boy with hematuria followed by acute urinary retention (Journal of Paediatric Surgeons of Bangladesh, 2018)
Acute frank hematuria followed by urinary retention in paediatric patients commonly occurs after trauma. A young boy hailing from a lake district of Bangladesh suffering from acute frank hematuria followed by urinary retention and painful abdominal swelling was evaluated by cystoscope. An intra-vesical dead leech was found and removed by a small suprapubic incision under cystoscopic guidance.Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (1): 20-21